Conventionalisation of Organic Agriculture: Betterment or Diminishment? - Putu Calista Gitta Kalyana (TIJAB (The International Journal of Applied Business), 2017)
Organic products become more popular as an alternative for consumption which are often perceived to be healthier and more environment-friendly. As the demand for organic products increases, the conventionalisation of organic agriculture practice becomes inevitable. The advantage of conventionalisation is arguable because although it can increase the production efficiency, the practice tends to disregard the principle of organic farming. This paper will discuss the issue through utilitarianism and justice theory framework. Utilitarianism perspective supports the conventionalisation of organic farming practice since the economic benefit would outweigh the cost of negative outcome from the damaged environment. Theory of justice offers opposing perspective by considering the marginalised farmer and the effect of the conventionalisation practice to the environment. According to the ecological justice perspective, conventionalisation of organic agriculture practice is unacceptable as it undermines the organic principle and proven to be detrimental for the small farmer where only the large operations perform the conventionalisation practice.